An open-source workflow for open-cell foams modelling: Geometry generation and CFD simulations for momentum and mass transport. (29th June 2022) - Agostini, Enrico; Boccardo, Gianluca; Marchisio, Daniele
Highlights: We developed an open-source workflow to characterize open-cell solid foams. The geometry generation is performed by using the computer graphics code Blender. Fluid flow and mass transfer are simulated using open-source CFD code OpenFOAM. From the CFD results permeability and filtration rate are calculated. The workflow (available online) is used to investigate a large number of different foams. Abstract: Open-cell foams are porous materials characterized by high porosity and large specific surface, industrially employed as catalyst supports or particulate filters. These materials can be modelled using periodic lattices, or with more complex approaches based on Voronoi tessellations. This work introduces, tests, and makes available an open-source workflow (Agostini, 2021 ) based on Blender that can reproduce great varieties of geometries with a limited cost for their modeling. An example of the exploration capabilities of this workflow is presented in the form of CFD simulations for flow field and mass transfer (performed with OpenFOAM) on the created geometries, eventually obtaining an effective particle deposition/filtration coefficient K d . The results are interpreted using constitutive equations and other functional forms depending on geometric parameters which prove to be insufficient in explaining the variations in filtration performance, highlighting the need for more detailed exploration, the objective for which this workflow was developed.